POLA KOMUNIKASI PROSTITUSI ONLINE PARA PEDILA DI DOLLY DAN KEMBANG KUNING - Akhsaniyah Akhsaniyah (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This study focusses on the Communication Patterns carried out by “Pedila” (Perempuan yang dilacurkan) in online prostitution in the Dolly and Kembang Kuning, Surabaya. The study uses a descriptive approach by using in-depth interviews. The subject who provided the information was a member of the “KOMPPAS” (Kelompok Pemberdayaan dan Penanganan Korban Traficking Surabaya)organization. Before and after the closure of the localization, even during the covid-19 pandemic until now, the practice of online prostitution is still exists. Using the theory of Interpersonal Communication Patterns and Gender, the results of this study is; There are two types of online prostitution communication patterns, first type 1, namely communication by pimps with guests to carry out negotiations and transactions, then communication by pimps with pedila. The second type is the communication carried out by Pedila directly with the Guest and conducting transactions, without intermediary Pimps. In the Dolly area, Pedila uses Type 1 a lot, while in the Kembang Kuning Pedila area many uses Type 2. Both are risky and vulnerable to crime, violence, and fraud. In Type 1, crime can be obtained from two actors, from Pimps and Guests. While Type 2, crime, violence, and fraud can come from the Guest.